Job Mobility in Australia during the COVID-19 Pandemic - Black, Susan; Chow, Emma (My University, 2022)
The COVID-19 pandemic has led to large disruptions to the Australian labour market. Initially, workers were less likely to change jobs because of the uncertain economic environment, the decrease in advertised jobs and the JobKeeper program that helped workers remain attached to their employers. More recently, job mobility has increased as workers have caught up on planned job changes or been encouraged by the strong labour market to change jobs, particularly in high-skilled roles experiencing strong labour demand. This article reviews developments in job mobility in Australia through the pandemic, and compares these outcomes to other advanced economies. It also examines the potential implications for wages; a high rate of job mobility tends to be associated with higher wages growth in a tight labour market, as employers in sectors with high demand for labour compete for new staff or raise wages to retain staff.
Bulletin
Keywords: Labour market